Fathers’ engagement in co-parenting practices to support early childhood social skills development - hidayati, fitrianur; Kristiana, Dian; Rusdiani, Nurtina Irsad (Pusat Studi Gender dan Anak, 2025)
Fathers’ involvement plays an important role in supporting the development of children’s social skills; however, in practice, this involvement is not always optimal. This study aims to explore the role of fathers in co-parenting practices related to the development of children’s social skills at TK Dharma Wanita Nguntoronadi, Magetan. This research employed a qualitative case study approach. The participants consisted of five fathers and two teachers, selected as key informants. Data were collected through semi-structured interviews, observations, and document analysis, and were analyzed using source triangulation to ensure data credibility. The findings indicate that: (1) the kindergarten has programs designed to foster children’s social skills, which require active father involvement to function optimally; (2) fathers are generally aware of their roles in nurturing children’s social development; (3) this awareness is reflected in their efforts to allocate quality time with their children; (4) fathers employ various interaction patterns to support social skill development, including teaching polite communication, engaging in play and recreational activities, maintaining dialogue, reading bedtime stories, sharing meals, and exercising together; and (5) fathers adopt diverse parenting strategies, often through discussion and coordination with their spouses. In conclusion, fathers play a significant and positive role in co-parenting practices that support the development of children’s social skills. Strengthening father involvement through collaborative parenting can further enhance children’s social competence.